Integrating Divine Values in Intercultural Communication Class - Hilma Pami Putri (Tamaddun, 2019)
This research focused on integrating the divine values in Intercultural Communication Class. One of the aims of this subject is to hindrance the communication problems in doing intercultural communication because everyone has different ways of thinking, feeling and doing with their own culture. There are many problems appear in communication if there is no understanding among culture, just like prejudice, racism, or even ethnocentrism. This was descriptive qualitative research, and the data got from observing and interpreting the lecturer’s ways of teaching in Intercultural Communication class especially in integrating the divine values on stereotyping. The result of this research shown that understanding about the negative impact of stereotyping is needed for the students to be a good communicator. In integrating divine values is a must in intercultural communication class in order to the students can create the convenience environment and effective communicator in talking to people which has different culture.